1998
DOI: 10.1002/(sici)1098-2744(199803)21:3<149::aid-mc1>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: Receptor-mediated events that may affect breast and other steroid hormone–dependent cancers

Abstract: Epidemiological studies have suggested a possible link between extremely low frequency electromagnetic fields (EMFs) and increased rates of certain cancers. One cancer that has been postulated to be associated with EMF exposure is breast cancer, for which increased rates have been reported among electricians. These cancer associations are weak, and the link to EMF exposures remains tenuous. Understanding the mechanisms by which EMFs could have biological effects will help in elucidating the risk, if any, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…It has been hypothesized that exposure to higher magnetic fields suppresses the nocturnal production and release of the hormone melatonin, which is assumed to have oncostatic capabilities; 31,32 however, the melatonin hypothesis has been proposed for breast cancer and hormone-dependent cancers rather than leukaemia. 33,34 Nevertheless, young children have higher melatonin levels than adults; 35 therefore, effects caused by reduced melatonin concentrations might be more marked. So far, there is weak supportive evidence for the melatonin hypothesis from human laboratory studies.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…It has been hypothesized that exposure to higher magnetic fields suppresses the nocturnal production and release of the hormone melatonin, which is assumed to have oncostatic capabilities; 31,32 however, the melatonin hypothesis has been proposed for breast cancer and hormone-dependent cancers rather than leukaemia. 33,34 Nevertheless, young children have higher melatonin levels than adults; 35 therefore, effects caused by reduced melatonin concentrations might be more marked. So far, there is weak supportive evidence for the melatonin hypothesis from human laboratory studies.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Presuming that melatonin has a real anticarcinogenic property, the breast-cancer-specific decrease may point to a mechanism with an intermediary role for oestrogens (Blask et al, 1991;Baldwin and Barret, 1998) in the biophysical/chemical pathway from visible light to endogenous melatonin secretion and, finally, to the development of breast cancer. It is pertinent, however, that it is not known.…”
Section: Discussionmentioning
confidence: 99%
“…This so-called melatonin hypothesis proposes that the suppression of melatonin secretion at night by artificial light increases breast cancer risk by increasing exposure to estrogen (168,169). Since the isolation of melatonin receptors and the finding of widespread expression of these receptors in neural and nonneural tissues (170,171), the scope of the melatonin hypothesis has expanded to include other mechanisms by which reduced melatonin concentrations may affect hormone homeostasis and induce breast and perhaps other cancers (172). A retrospective survey found that severely blind women had about half the incidence of breast cancer of women with normal vision (173).…”
Section: Circadian Clock and Breast Cancermentioning
confidence: 99%